Ozone therapy by rectal insufflation in dogs: safety and oxidative stress - a randomized cross-over study - de Oliveira, Paula Lima [UNESP]; Mendonça, Mariana Orlandini; Gonçalves, Geovanna Santos; Franco, Isadora Gimenez; Jané, Daniela Ribas [UNESP]; de Oliveira Martins, Tainara; Bosculo, Maria Rachel Melo; Montechiesi, Daniela Fernandez; Zamboni, Vinicius Aquiles Gomes [UNESP]; Floriano, Beatriz Perez; de Almeida, Breno Fernando Martins [UNESP] (Springer Nature, 2024)
Ozone therapy acts in the body inducing controlled oxidative stress, thereby improving the antioxidant, immune and circulatory responses. However, very little is known about how this therapy affects oxidative stress indicators in dogs. We aimed to assess the clinical, hematological, biochemical and oxidative stress parameters of healthy dogs subjected to ozone therapy and oxygen therapy by rectal insufflation. Ten healthy dogs were allocated into three experimental groups in a cross-over design: control, without intervention; ozone, which received 100 µg of O3/kg through rectal insufflation; and oxygen, which received an ozone-equivalent volume of medicinal O2 through rectal insufflation. Dogs received four applications weekly and were followed up until the seventh week. Ozone therapy significantly increased the weight, mean corpuscular volume and mean platelet volume and decreased total cholesterol of treated dogs. Regarding oxidative stress, ozone therapy reduced total antioxidant capacity by ferric reduction (TAC-FRAP) in D7 compared with baseline and the control, significantly increased total antioxidant capacity by cupric reduction (TAC-CUPRAC) in D42 and D49 compared with the control group, caused an increase in uric acid compared with the oxygen group and decreased lipid peroxidation on D21 compared with the control group. In conclusion, ozone therapy through rectal insufflation causes transient oxidative stress followed by an antioxidant response and discreetly interferes with a few clinical, hematological and biochemical variables in healthy dogs, although variables still remained within the reference ranges for the species, thus proving the safety of the therapy. Furthermore, oxygen therapy causes oxidative stress without inducing a subsequent antioxidant response.
Keywords: Antioxidant; Free radicals; Ozonotherapy